Characterization of bluetongue virus serotype 28. Issue 1 (10th September 2019) - Bumbarov, Velizar; Golender, Natalia; Jenckel, Maria; Wernike, Kerstin; Beer, Martin; Khinich, Evgeny; Zalesky, Olga; Erster, Oran
Abstract: Bluetongue virus ( Reoviridae; Orbivirus, BTV), which is usually transmitted by biting midges, affects wild and domestic ruminants worldwide, thereby causing an economically important disease. Recently, a putative new BTV strain was isolated from contaminated vaccine batches. In this study, we investigated the genomic and clinical characteristics of this isolate, provisionally designated BTV‐28. Phylogenetic analysis of BTV‐28 segment 2 (Seg‐2) showed that it is related to Seg‐2 from BTV serotypes 4, 10, 11, 17, 20 and 24, sharing 64%–66% identity in nucleotide sequences (nt) and 59%–62% in amino acid (aa) sequences of BTV VP2. BTV‐28 Seg‐6 is related to the newly reported XJ1407 BTV isolate, sharing 76.70% nt and 90.87% aa sequence identity. Seg‐5 was most closely related to a South African BTV‐4 strain, and all other segments showed close similarity to BTV‐26. Experimental infection by injection of 6‐month‐old ewes caused clinical signs in all injected animals, lasting from 2 to 3 days to several weeks post‐infection, including high body temperature, conjunctivitis, nasal discharge and rhinitis, facial oedema, oral hyperaemia, coronitis, cough, depression and tongue cyanosis. Naïve control animals, placed together with the infected sheep, displayed clinical signs and were positive for viral RNA, but their acute disease phase was shorter than that of BTV‐injected ewes. Control animals that were kept in a separated pen did not display any clinical signs and were negative for viral RNA presence throughout the experiment. Seroconversion was observed in the injected and in one of the two contact‐infected animals. These findings demonstrate that BTV‐28 infection of sheep can result in clinical manifestation, and the clinical signs detected in the contact animals suggest that it might be directly transmitted between the mammalian hosts.